Toxin production and drug resistance profiles of pediatric methicillin-resistant Staphylococcus aureus isolates in Tehran - Mozhgan Esmaeili Benvidi; Hamidreza Houri; Zohreh Ghalavand; Bahram Nikmanesh; Hadi Azimi; Roghayeh Samadi; Narges Nodeh Farahani; Gita Eslami (Journal of Infection in Developing Countries)
Introduction: Staphylococcus aureus is known to be a major cause of skin and soft tissue infections, pneumonia and invasive diseases. In this study, attempts were made to examine the prevalence of tsst-1, eta, etb, and luk-PV genes among methicillin-resistant S. aureus (MRSA) isolated from children in Tehran.